2015
DOI: 10.1111/acer.12726
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Fetal Alcohol Syndrome in a South African City with a Predominantly Black African Population

Abstract: Prevalence of FAS is high in both Galeshewe and Roodepan, and the lack of prior diagnoses indicates that awareness remains low. The maternal mortality rate was especially high in Galeshewe. The unexpectedly high burden of FAS in an urban area with predominantly Black African population mandates extension of surveillance and intervention measures in southern Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 35 publications
0
46
1
Order By: Relevance
“…[1][2][3][4][5][6] Drinking during pregnancy has been correlated with negative pregnancy outcomes including an increase in spontaneous abortion, fetal growth retardation, premature delivery, abruptio placentae and breech presentations. [7] During the first trimester, alcohol can change the way in which cells grow and organise them selves and result in abnormalities of the face, heart, brain, limbs and urogenital system.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Drinking during pregnancy has been correlated with negative pregnancy outcomes including an increase in spontaneous abortion, fetal growth retardation, premature delivery, abruptio placentae and breech presentations. [7] During the first trimester, alcohol can change the way in which cells grow and organise them selves and result in abnormalities of the face, heart, brain, limbs and urogenital system.…”
mentioning
confidence: 99%
“…Since 1997, various prevalence studies in SA have revealed FAS rates as high as 26 per 1 000 in Gauteng; [13] 64, 74.7, and 119.4 per 1 000 in Upington, Kimberley and De Aar, Northern Cape, respectively; [14,15] 6.7, 9.6 and 100 per 1 000 in the Saldanha Bay Municipality, the Witzenberg sub-district, and Aurora on the West Coast, respectively; [16] and 290 per 1 000 in the Winelands area. [17] The SA studies involve all the cultural groups living in these rural, peri-urban and urban communities (Fig.…”
Section: Fas and Fasd Prevalence Studies In South Africamentioning
confidence: 99%
“…The dysmorphology features included the primary facial features of FAS such as short palpebral fissures, narrow upper vermillion border, smooth philtrum of the upper lip. [15] School educators could also refer consented grade 1 learners with learning, health or psychosocial problems.…”
Section: Screening and Clinical Assessmentsmentioning
confidence: 99%
See 2 more Smart Citations